Investigation on effectiveness of different binder in geocomposite / Sayani Khorim - Khorim, Sayani (2006)
This study investigates the California Bearing Ratio (CBR) characteristic of shredded tire geocomposite and the effectiveness of different types of binders (Ordinary Portland Cement, OPC and Rice Hush Ash, RHA) in shredded tire geocomposite. This project began with intensive literature review followed by mix design. Three preliminary tests namely particle size distribution test, specific gravity test and bulk densities test were then conducted to characterize the shredded tire. The main scope of this study is laboratory CBR test. A total of five CBR test series were conducted to investigate the effect of curing day, repeatability of test specimen, effect of soaking and non soaking, effect of cement content and effect of RHA content. To ensure the consistency of the test results, standardization and control was enforced on casting process and water-cement ratio. The CBR test results revealed that higher curing day and cement content increase the CBR of shredded tire geocomposite. On the contrary, a higher RHA content will reduce the CBR of the geocomposite. Higher CBR is also observed for non-soaking curing condition. In conclusion, this study has identified Ordinary Portland Cement (OPC) as a suitable binder to form shredded tire geocomposite.